Artificial Intelligence in Education: The Power and Dangers of ChatGPT in the Classroom - Al-Marzouqi, Amina; Salloum, Said A.; Al-Saidat, Mohammed; Aburayya, Ahmed; Gupta, Babeet (Studies in Big Data, 2024)
XI, 675 p. 72 illus., 61 illus. in color.